Nutrients use efficiency by modern hybrids of maize under arid conditions of the Forest-Steppe - Kharchenko О.V.; Petrenko, S.V.; Sobko, M.G.; Medvid, S.I.; Zakharchenko, E.A. (AgroChemistry and Soil Science, 2021)
The nutrient use efficiency of maize hybrids from the soil or through fertilizers is considered. Cultivation of modern hybrids requires determining the necessary rate of fertilizer to get the planned yield, taking into account their potential productivity and weather conditions. In the absence of data of nutrient uptake for new hybrids, it is proposed to use an indicator of their level of intensity, which is calculated by the ratio of the actual yield and its normative (calculated) value. Studies were conducted in 2018 and 2019 in the fields of the Institute of Agriculture of the Northeast of the National Academy of Agrarian Sciences of Ukraine. Soil – chernozem typical leached (Endocalcis Chernozem). Three maize (Zea mays L.) hybrids of Ukrainian selection were used: Zoryany (FAO 190), Leleka (FAO 260) and Donor (FAO 310). The vegetation seasons 2018-2019 were characterized as very arid (hydrothermal coefficient of Selianinov (HTC) 0.45-0.46). The calculated rate intensity of hybrids on average of two years was 1.07 at sites without fertilizers, and 1.36 at sites with fertilizers (N100 P45 K45). The efficiency of soils N,P,K use increases by application of mineral fertilizers. The nutrients output from the soil: nitrogen ‒ 53.8-71.4 %, phosphorus ‒ 20.0-26.6 % and potassium ‒ 65.4-86.8 %. The relative effect of fertilizers on the yield decreases, therefore, rate of natural fertility in the growth of the crop on fertilized soil increases. Due to the natural fertility of soils, the yield of all hybrids increased by an average of 1.33-1.46 t/ha with N100 P45 K45 applying. The dependence of yield of all maize hybrids on hydrothermal conditions in June was obtained. It was found that, all other things being equal, the yield is directly correlated with the FAO index of the hybrid. The payback of mineral fertilizers is estimated as 0.86-1.14 t / c